Quantification of acid-base interactions based on contact angle measurement allows XDLVO predictions to attachment of Campylobacter jejuni but not Salmonella - Nguyen, V.; Chia, T.; Turner, M.; Fegan, N.; Dykes, Gary (2011)
Acid–base (AB) interactions play the most important role in bacterial attachment to surfaces and can be quantified based on electron donor/electron acceptor data from contact angle measurement (CAM) according to the extended Derjaguin–Landau–Verwey–Overbeek (XDLVO) theory. It follows that the XDLVO theory could fail to explain attachment numbers if differences in AB interactions between strains are not apparent by CAM. This study aimed to investigate the validity of the above assumptions by comparing empirical data on attachment of six bacterial strains (three strains of Campylobacter jejuni and three strains of Salmonella) to stainless steel and XDLVO theory predictions. A significant difference (P < 0.05) in AB interactions, apparent by CAM, between C. jejuni strains allowed prediction of attachment of this species by the XDLVO theory. However, the theory failed to explain the attachment numbers for Salmonella due to similar AB interactions, as established by CAM, between the three Salmonella strains. Qualitative analysis of AB interactions by microbial adhesion to solvents (MATS) revealed a significant difference (P < 0.05) in electron donor property between the three Salmonella strains suggesting that these strains may differ with respect to AB interactions. No significant correlation with respect to electron donor property (P = 0.502, r2 = 12%) was apparent between CAM and MATS. These data suggest that CAM may not always reflect exactly AB interactions and that the difference in the outcomes from MATS and CAM should be considered when the XDLVO theory is used to predict bacterial attachment to surfaces.